Antibacterial Properties of Binuclear Zn(II)-Azomethine Complexes Derived from Diaminodiphenylsulphide Bridged Spacer - Sarwar, Aziza; Nabi, Nusrat; Naureen, Bushra; Bibi Sherino; Ellahi, Mujtaba; Panezai, Hamida (Scientific Inquiry and Review, 2022)
The current research aims to study the antimicrobial resistance of microbes against once-effective treatments for the development of new drugs. Accordingly, three binuclear Zn(II)-Schiff bases complexes, ZnLa-ZnLc were prepared by the direct reaction of the ligands La-Lc with Zn(II) ions in equimolar ratios bearing salicylaldehyde with OH, NO2, and Cl functional groups. The synthesized compounds ZnLa-ZnLc were evaluated against gram-positive (E. faecalis, S. mutante, and S. aureus) and gram-negative (E. coli, S. Typhi, and P. aeruginosa) bacterial strains by agar well diffusion and broth microdilution technology. Minimum inhibitory concentration (MIC90) values ​​were calculated using a microplate reader at 550 nm for optimal results. Binuclear Zn(II) complexes showed superior antibacterial activity as compared to their parent Schiff base ligands, which were clearly investigated from their respective MIC values ​​and the diameter of the growth inhibitory zone. Additionally, E. faecalis were not active against the Schiff base ligand La-Lc, whereas their complexes ZnLa-ZnLc showed biological activity in an inhibition zone ranging from 9-10 mm to E. faecalis. In general, Schiff base 3,4-dihydroxy as well as its metal complex showed excellent antibacterial activity with zone of inhibition (13-26 mm) and (10-28 mm), respectively. Therefore, the synthesized compounds may be promising entities in the field of medicine.